2012
DOI: 10.1002/hed.23128
|View full text |Cite
|
Sign up to set email alerts
|

Effect of erlotinib on epidermal growth factor receptor and downstream signaling in oral cavity squamous cell carcinoma

Abstract: Purpose To determine if there are differences in biomarker modulation and EGFR degradation between tumor and the normal mucosa following treatment with an EGFR inhibitor, erlotinib, in head and neck cancer. Methods Patients with primary oral cavity squamous cell cancers received a course of erlotinib, 150 mg qd for 7 days prior to surgical resection. Tumor and normal mucosa biopsies were obtained both pre and post erlotinib. Changes in known markers of EGFR activity (phospho, AKT, STAT3) were measured by imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 40 publications
1
21
1
Order By: Relevance
“…Assessment of each autophosphorylation site is limited by the quality of available antisera, particularly for IHC analyses. As measured by immunoblotting, expression of pEGFR on a nonautophosphorylation site, pY845, was reportedly decreased in 7 HNSCC patients treated with 7 days of erlotinib on a window trial (29). Curiously, pY845 has been previously associated with Src signaling (30).…”
Section: Resultsmentioning
confidence: 99%
“…Assessment of each autophosphorylation site is limited by the quality of available antisera, particularly for IHC analyses. As measured by immunoblotting, expression of pEGFR on a nonautophosphorylation site, pY845, was reportedly decreased in 7 HNSCC patients treated with 7 days of erlotinib on a window trial (29). Curiously, pY845 has been previously associated with Src signaling (30).…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, inhibiting EGFR-Stat3 pathway in 4-nitroquinoline-1-oxide (4-NQO-) induced murine model of oral carcinogenesis by erlotinib, a small molecule inhibitor of EGFR, inhibited development of preneoplastic lesions and oral tumors by approximately 70% with a concomitant decrease of Stat3 levels in erlotinib-treated mice [56]. Similarly, primary human oral cavity squamous cell cancers showed reduced levels of both EGFR and p-Stat3 after treatment with erlotinib compared to pretreated paired tissue [57]. Moreover, combined molecular targeting of Stat3 sensitizes cells to radiotherapy and small molecule chemotherapeutic agents in vitro [58, 59].…”
Section: Stat3 and Human Skin Cancermentioning
confidence: 99%
“…Studies have shown an increase in overall survival of almost 20 months in HNSCC patients who received targeted therapy against EGFR in combination with radiotherapy compared to radiotherapy alone . At the same time, only a subset of HNSCC patients receiving cetuximab actually respond to treatment, underlining the need for a means to tailor treatments to individual patients .…”
Section: Introductionmentioning
confidence: 99%